Análisis de los costos de producción del banano orito orgánico en el cantón Bucay de la provincia del Guayas para la exportación en el mercado de Estados Unidos - Tomalá Mendoza, Ingrid Yomaira (2020)
The present degree work was focused on the cost structure study and analysis and the incidence of external and internal factors to the production process of eleven small producers of organic orito bananas, which together have a total area of twenty hectares in Bucay Canton in Guayas province. It is important to highlight that, in those lands approximately ten years ago they exported this crop in small quantities to the United States, but it could be evidenced that the settlers stopped doing so due to different factors such as lack of capital, not good irrigation system and that for not having constant training plus the climatic effects stopped exporting. Moreover,…….